A novel exploration of the support needs of people initiating insulin pump therapy using a social network approach: a longitudinal mixed‐methods study. Issue 2 (7th November 2019) - Reidy, C.; Foster, C.; Rogers, A.
Abstract: Aims: To establish what practical and emotional means of support are required on initiation of insulin pump therapy and how needs change over time, using GENIE, a social network intervention. Methods: The study's longitudinal design used semi‐structured interviews, surveys (PAID, CLARKE) and HbA1c values at time of pump initiation, and at 3 and 6 months. Interviews used GENIE to capture participants' expectations and experiences of pump therapy and associated support and resources. Thematic analysis was used with sequential, time‐ordered matrices. Results: A total of 16 adults undertook 47 interviews. A total of 94 services, resources and activities were acquired, while tally, frequency and value of network members increased over time. The novelty of pump therapy impacted on participants' self‐management needs. Key themes included: 1) the independent nature of managing diabetes; 2) overcoming the challenges and illness burden associated with pump use; 3) the need for responsive and tailored emotional and practical support; and 4) useful resources when incorporating pump therapy. GENIE was thought to be novel and beneficial. Conclusions: A social network approach determined what resources and support people with diabetes require when incorporating a new health technology. Visualisation of support networks using concentric circles enabled people to consider and mobilise support and engage in new activities as their needs changed. The novelty of pump therapy creates new illness‐related work, but mobilisation of personally valued flexible, tailored support can improve the process of adaptation. What's new?: The need for self‐management support is heightened when a new technology is introduced, requiring new or renewed knowledge, confidence and resources and much fine‐tuning over time. The intervention in the present study offered a positive disruption to self‐management by prompting reconsideration of network members and how they impact on self‐management as well as an avenue to connect to new activities and sources of support. Social support mapping demonstrated a rich range of network members, ranging from partners, to family members, peers, pets, community groups, friends and objects, (for example, bicycles, glucose monitors) of varying types, numbers, frequency and value. There was a return on investment for non‐judgemental, accessible self‐management support and education provided by specialist pump clinics.